2017
DOI: 10.3390/molecules22071113
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Reveals an Important Role for the PPAR Signaling Pathway in DBDCT-Induced Hepatotoxicity Mechanisms

Abstract: A patented organotin di-n-butyl-di-(4-chlorobenzohydroxamato)tin (DBDCT) with high a antitumor activity was designed, however, its antitumor and toxic mechanisms have not yet been clearly illustrated. Hepatic proteins of DBDCT-treated rats were identified and analyzed using LC-MS/MS with label-free quantitative technology. In total, 149 differentially expressed proteins were successfully identified. Five protein and mRNA expressions were involved in the peroxisome proliferator-activated receptor (PPAR) signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The PPARγ target genes that appear to be predominantly altered by the PN diet and normalized by FOLE are CD36 and SCD1. Prior studies have established roles for omega-3 fatty acid-mediated GPR120 signaling and, independently, PPARγ in modulating hepatic lipid metabolism [25][26][27]. Recently, a relationship has been established between GPR120 signaling and PPARγ activity in modulating lipid metabolism and adipocyte function [28].…”
Section: Discussionmentioning
confidence: 99%
“…The PPARγ target genes that appear to be predominantly altered by the PN diet and normalized by FOLE are CD36 and SCD1. Prior studies have established roles for omega-3 fatty acid-mediated GPR120 signaling and, independently, PPARγ in modulating hepatic lipid metabolism [25][26][27]. Recently, a relationship has been established between GPR120 signaling and PPARγ activity in modulating lipid metabolism and adipocyte function [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research found that the gene expressions of platelet glycoprotein 4 ( CD36 ), fatty acid binding protein ( FABP ), enoyl-CoA hydratase ( EHHADH ), and 3-ketoacyl-CoA thiolase B ( ACAA1 ), which are involved in fatty acid β oxidation, were increased in Buffalo Rat liver cells (BRL) treated with DBT and Di- n -butyl-di-(4-chlorobenzohydroxamato) tin (IV) (DBDCT) [ 12 ]. Our present research showed that the TG contents as well as the genes involved in lipogenesis, including SREBP1C, SCD1 , FASN, and GPAT1, were dosage-dependently decreased when cells were treated with DBTD at concentrations higher than 0.25 μmol/L ( Figure 3 and Figure 4 ), while the gene expressions of PPARα , ACOX1 , and CPT1 in HL7702 cells were increased ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous proteomics research on rat livers had found that DBTs mainly affected the proteins related to lipid anabolism and catabolism [ 12 ]. The TG metabolism in the liver is regulated by the mammalian target of rapamycin (mTOR) pathway through modulating peroxisome proliferator-activated receptor alpha (PPARα) and sterol regulatory element-binding protein 1C (SREBP1C) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure concentration of phthalate metabolites such as DEHP and mono (2-ethylhexyl) phthalate (MEHP) positively correlated with insulin resistance and abdominal obesity in American male adults [39][40][41]. Di-n-butyl-di-(4-chlorobenzohydroxamato) tin (DBDCT), an organotin with high antitumor activity, was also demonstrated to induce notable toxicity in rat liver tissue via the PPAR signaling pathway [42]. DBDCT treatment aroused acute and focal necrosis and Kupffer cell hyperplasia in rat liver.…”
Section: Ppars In Hepatotoxicitymentioning
confidence: 99%
“…The decreased expression levels of cluster of differentiation 36 (CD36), fatty acid binding protein 4 (FABP4), enoyl-CoA hydratase and 3-hydroxyacyl CoA dehydrogenase (EHHADH), acetyl-CoA acyltransferase 1 (ACAA1), phosphoenolpyruvate carboxykinase (PEPCK), PPARα, and PPARγ in DBDCT-treated liver tissue were indicated by proteomics. Furthermore, the toxic effect was alleviated by PPARγ blocking agent T0070907 [42,43]. Additionally, organotins, the major components of agricultural fungicides and pesticides, were documented to exert similar functions as PPARγ and PPARβ ligands, which promote weight gain and increase fat storage by target gene induction in liver [44].…”
Section: Ppars In Hepatotoxicitymentioning
confidence: 99%